Intersectionality at work: How disability, employer biases, and SME constraints shape employment outcomes for persons with disabilities - Simranpreet Kaur Hansaram; Rudzi Munap (Environment and Social Psychology, 2025)
Drawing from Intersectional theory, this qualitative study explores two research questions: the employment challenges faced by persons with disabilities (PWDs) and the employers’ perception of small and medium-sized enterprises (SMEs) in hiring PWDs. A thematic analysis is adopted and addresses two main research questions by using semi-structured interviews with ten SMEs operators. The results for the first research question point to four related problems: employers not knowing enough about the skills of PWDs and not recognizing them, common stereotypes and societal views, physical barriers and infrastructure issues in the workplace, and employers concerned about cost and resources. The second research question revealed SMEs employers’ reluctance to hire persons with disabilities because of a lack of understanding of their skills and perceive them as difficult to work with. It also recognizes potential facilitators, like the importance of variety and the practicality of focused interventions such as specialized training, financial incentives such as tax breaks, and peer-support networks. Results from this study demonstrated that hiring people with disabilities is affected by a combination of factors, namely, their disabilities, employer biases, and the restrictions faced by SMEs. These indicate the importance of multi-tiered interventions that deal with both structural and attitudinal barriers, thus, the study importance in theoretical and practical effects. Most importantly, it promotes the hiring of PWDs as a shared responsibility between employers, policy makers, and society.